Membentuk Keputusan Bisnis yang Etis: Peran Pendidikan Etika Profesi Bagi Mahasiswa Akuntansi - Irwansyah Saputra, Wiyanda Anggraini, Risma Adekantari, Selfi Pebrianti, Farel Nasril Ilham, Rizky K (PT Wahana Global Education, 2025)
The number of cases of ethical violations in the accounting profession, both in the country and around the world, shows how important it is to build a firm moral foundation for prospective accountants. Professional ethics education is considered very important to shape the attitudes and behavior of accounting students who will become business decision makers in the future. This study aims to analyze the role of professional ethics education in shaping ethical business decision making among accounting students. The method used is a literature study with a qualitative descriptive approach through a critical review of various journals and scientific articles. The results showed that business and professional ethics education has a positive effect on students' ethical behavior. This education increases students' understanding of integrity and accountability, and helps them more maturely handle ethical dilemmas. Nonetheless, there are other issues that arise. These include the discrepancy between theoretical understanding of what happens in the real world and the impact of social environmental pressures on students' moral consistency. In conclusion, accounting students are educated about professional ethics so that they can make ethical business decisions. However, this education needs to be improved with a more relevant and applicable approach.